Efficiency Analytics of NCAA Division I College Football Programs - Frank A. Bouchet; Mike Troilo; Wen-Chyuan Chiang; Jennifer Shang (Journal of Applied Sports Management, 2022)
College athletics are a multi-billion dollar industry in the United States, but how well do university athletic programs employ their resources? The question is germane in light of increasing costs of higher education and scrutiny of university budgets. This study furnishes a template to weigh the tradeoffs inherent in collegiate sports, which is the main contribution of the paper. A dataset of 117 American college football programs from 2011-2015 is analyzed using DEA and AHP methods to assess the efficiency and perception of these programs. The result is the aforementioned framework measuring the programs' success and answers the question of program efficiency.
Keywords: AHP; DEA; College Sports; Resource Allocation; Sport Performance